CAB DIRECT IS THE FOCUS OF A SCIENTOMETRIC ANALYSIS FROM 2011 TO 2013: BEANS SCIENTIFIC RESEARCH ARTICLES - L., Rajendran (International Journal of Research -GRANTHAALAYAH, 2021)
Bean researches from 2011 to 2013 were collected from the CAB Direct Online database using scientometric analysis. Between 2011 and 2013, 36 papers were written, according to the report, with 21 papers being highly published in 2011. The most common topic among scientists interested in beans research was Biology and breeding of food legumes, with 13 papers (36.1%), followed by Nutrient deficiencies of field crops: guide to diagnosis and management, with 5 papers (13.8%). Combating micronutrient deficiencies: food-based approaches; Crop plant anatomy; Natural products in plant pest management; and African vegetable production and marketing: socioeconomic research papers published in the same journal (5.55%). Indian scholars have written more papers on bean studies than authors from other countries. Gujarat, Jharkhand, Tamil Nadu, Karnataka, Uttar Pradesh, Andhra Pradesh, West Bengal, Bihar, Madhya Pradesh, and Chattisgarh are the major bean-growing states in India. Bean trade outnumbers all other crops combined in India, and global demand for Indian beans is increasing.